Serological and histological follow up of chronic hepatitis B infection. Issue 8 (August 1989) - Ruiz-Moreno, M; Camps, T; Aguado, J G; Porres, J C; Oliva, H; Bartolomé, J; Carreño, V
Abstract : In order to study the clinical, serological, and morphological evolution of chronic hepatitis B virus infection in childhood, a prospective study has been carried out. A total of 90 children with a chronic infection were followed up for a mean (SD) of 3 (1.8) years. At the beginning of the study, 61 children were asymptomatic and 77 were household contacts of chronic carriers. Serologically 77 were hepatitis B e antigen (HBeAg) positive and 71 of them were positive to hepatitis B virus DNA. The mean alanine aminotransferase activities were higher among HBeAg positive patients than in antihepatitis B e (anti-HBe) positive ones. The most severe histological damage was also found among HBeAg positive patients. The annual seroconversion rate was 14%. A significant increase in the alanine aminotransferase activity was observed 13 (5.6) months before appearance of anti-HBe in the 85% of cases. Among anti-HBe positive patients, the alanine aminotransferase activities were normal in all except three (19%), two of whom had intrahepatic delta antigen. An increase in the histological activity was observed among patients who maintained HBeAg presence while an amelioration of liver damage was observed in anti-HBe carriers.